Literature Review: Interactive Media of PAI Learning Based on Android Games Using the Game Development Life Cycle (GDLC) Method - Purnama Sari, Devi; Gilang Maulana Jamaludin (Indonesian Journal of Islamic Education, 2025)
This study explores the effectiveness of interactive learning media based on Android games tailored for Islamic education, employing the Ganes Development Life Cycle (GDLC) approach. A literature review of publications from 2021 to 2024 reveals that this media enhances student’s learning motivation, provides engaging and interactive learning experiences, and deepens comprehension of the material. The structured methodology of GDLC ensures efficient development of the media. In conclusion, Android-based educational games significantly improve the quality of Islamic Education (PAI) learning and align with the demands of modern digital education.